Pengaruh Literasi Keuangan, Teknologi Informasi, Kepercayaan dan Sumber Daya Manusia Terhadap Minat Menabung Gen Z pada Bank Syariah - Alvaro Wisnu Zaraneta; Lintang Kurniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of financial literacy, information technology, trust, and human resources on Generation Z’s saving interest in Islamic banks. The research employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to Generation Z respondents in Surakarta City and analyzed using multiple linear regression analysis. The results indicate that financial literacy and trust have a significant partial effect on Generation Z’s saving interest in Islamic banks. Meanwhile, information technology and human resources do not show a significant partial effect. However, simultaneously, financial literacy, information technology, trust, and human resources significantly influence Generation Z’s saving interest in Islamic banks. These findings suggest that improving Islamic financial literacy and strengthening trust among Generation Z are key factors in increasing saving interest in Islamic banking. This study is expected to provide insights for Islamic banks in formulating strategies to enhance financial inclusion and market penetration among younger generations.